The public and patient involvement imperative in Ireland: Building on policy drivers - Gilfoyle, Meghan; MacFarlane, Anne; Hannigan, Ailish; Niranjan, Vikram; Hughes, Zoe; Salsberg, Jon (Frontiers in Public Health, 2022)
What can we learn from the history of Public and Patient Involvement (PPI) in healthcare and research across global jurisdictions? Depending on region and context, the terminology and heritage of involvement in research vary. In this paper, we draw on global traditions to explore dominant themes and key considerations and critiques pertaining to PPI order to inform a PPI culture shift in Ireland. We then describe the heritage of PPI in Ireland and present the case for combining methodological imperatives with policy drivers to support and encourage meaningful involvement. Specifically, we propose that PPI can be enriched by the theory and processes of participatory health research; and that implementation requires concurrent capacity building. We conclude with a call for Irish researchers (authors of this paper included) to consider the conceptual complexities and nuances of a participatory approach to build on the policy imperatives driving PPI and to contribute to the international evidence base and research culture. Specifically, we call for Irish health researchers and funders to consider and reflect on: 1) the rich literature of PHR as a resource for enacting meaningful PPI; 2) the roots and origins of varying participatory health research methods; 3) how community/patient groups can lead health research; and 4) co-learning and partnership synergy and create space for both academic and community expertise.